Solenosmilia variabilis-bearing cold-water coral mounds off Brazil - Raddatz, Jacek; Titschack, Jürgen; Frank, Norbert; Freiwald, André; Conforti, A.; Osborne, Anne; Skornitzke, Stephan; Stiller, Wolfram; Rüggeberg, Andres; Voigt, S.; Albuquerque, A. L. S.; Vertino, A.; et al. (Coral reefs, 2020)
Cold-water corals (CWC), dominantly Desmophyllum pertusum (previously Lophelia pertusa), and their mounds have been in the focus of marine research during the last two decades; however, little is known about the mound-forming capacity of other CWC species. Here, we present new 230Th/U age constraints of the relatively rarely studied framework-building CWC Solenosmilia variabilis from a mound structure off the Brazilian margin combined with computed tomography (CT) acquisition.
Published online: 11 December 2019
Gesehen am 07.04.2020